TBOE maturity assessment model for standard digitalization: An empirical analysis using AHP and Delphi method - Xize Liu; Bingyan Zhang; Yiyi Wang; Nana Niu; Jingsheng Li; Xinrui Hu (PLoS ONE, 2026)
With the advancement of digital, networked, and intelligent transformations in the economy and society, the integration of standardization with digital technology has garnered significant attention globally. Consequently, the digitization of standards has become an inevitable trend. This study aims to address the challenges in standard digitization by proposing a comprehensive framework. Distinct from the traditional TOE framework, this study explicitly introduces the Business dimension as an independent analytical factor, constructing the novel TBOE (Technology-Business-Organization-Environment) model that better captures the business-driven nature of standard digitalization. Through factor analysis, key influencing factors are identified. A maturity assessment model is developed, categorizing the digitization process into three stages. The model incorporates rigorous indicator normalization procedures and stage division thresholds derived from the Gartner Hype Cycle framework. Sensitivity analysis confirms the robustness of the model under weight perturbations and measurement uncertainties. An empirical analysis within the power industry validates the model’s applicability, providing theoretical guidance and a practical toolkit for standard digitization across various sectors.